2000
DOI: 10.1038/35000025
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Snail controls epithelial–mesenchymal transitions by repressing E-cadherin expression

Abstract: The Snail family of transcription factors has previously been implicated in the differentiation of epithelial cells into mesenchymal cells (epithelial-mesenchymal transitions) during embryonic development. Epithelial-mesenchymal transitions are also determinants of the progression of carcinomas, occurring concomitantly with the cellular acquisition of migratory properties following downregulation of expression of the adhesion protein E-cadherin. Here we show that mouse Snail is a strong repressor of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

136
2,891
7
40

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,226 publications
(3,112 citation statements)
references
References 44 publications
136
2,891
7
40
Order By: Relevance
“…As previously reported, we noted that epithelial cells expressing Snail exhibit morphologic features consistent with EMT and concomitant downregulation of specific junctional proteins (Batlle et al, 2000;Cano et al, 2000;Ohkubo and Ozawa, 2004;Supplementary Figures 1a-e, 2a-d).…”
supporting
confidence: 85%
“…As previously reported, we noted that epithelial cells expressing Snail exhibit morphologic features consistent with EMT and concomitant downregulation of specific junctional proteins (Batlle et al, 2000;Cano et al, 2000;Ohkubo and Ozawa, 2004;Supplementary Figures 1a-e, 2a-d).…”
supporting
confidence: 85%
“…Loss of both cell-cell adhesion and cellular differentiation is one of the characteristics of malignant cells, and this has been reported extensively to correlate with E-cad down-regulation (Bracke et al, 1996;Endo et al, 2000;Huang et al, 1999;Takeichi, 1993). Reduced E-cad expression due to transcriptional repressor Snail around CDH1 promoter region may participate in certain steps of carcinogenesis by reduction of intercellular adhesiveness, which may result in initiation of invasion and destruction of normal tissue morphology (Batlle et al, 2000;Cano et al, 2000). The present study demonstrated the presence of Snail mRNA in HuL-1, Changliver, HLE and HLF cells, but not in Hep-G 2 cells detected by RT -PCR, these patterns were further proved by ISH in tumours, where Snail mRNA signals expressed in each tumour sections induced by HuL-1, Changliver, and HLF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Snail was described to contribute to repress transcription of E-cad gene by binding to the E-boxes of the CDH1 promoter (Giroldi et al, 1997). There is a strong inverse correlation between the Snail and E-cad expression in a panel of epithelial and dedifferentiated cells derived from carcinomas of various etiologies, including oral squamous carcinoma, breast, pancreas, colon, bladder cancer, melanomas, and fibroblast (Batlle et al, 2000;Cano et al, 2000;Yokoyama et al, 2001). However, the correlation of Snail and E-cad is not yet known in human HCC.…”
mentioning
confidence: 99%
“…Upregulated expression of Snail1 is detected in cell lines that have adopted a mesenchymal phenotype (De Craene et al, 2005). Moreover, ectopic expression of Snail1 promotes an EMT in epithelial tumor cell lines (Batlle et al, 2000;Cano et al, 2000), characterized by decreased expression of epithelial genes, such as E-cadherin, and upregulation of mesenchymal genes. Repression of epithelial genes by Snail1 requires the binding of the C-terminal domain of this protein to 5 0 -CACCTG-3 0 elements present in these promoters and the interaction of the SNAG Snail1 sequence with co-repressors (Thiery et al, 2009;Garcı´a de Herreros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%